Cytologic Diagnosis of Chondrosarcoma on Fine Needle Aspiration Cytology: A Challenge! - Seema R. Balasubramaniam; Vishrabdha R. Pawar (Journal of Krishna Institute of Medical Sciences University, 2019)
Chondrosarcoma is a malignant tumour of cartilage, usually named and classified by anatomic location. Primary chondrosarcoma is the third most common primary tumour of bone, after myeloma and osteosarcoma. Commonest sites of presentation are pelvic bones, long bones and relatively rare in ribs. Here we report a case of 75 year old male who presented with a swelling over the left lower lumbar region, which increased gradually in size in three months. The swelling was not associated with pain or trauma. After initial clinical workup, he was referred to the Radiology Department, for Computerized Tomography (CT) scan. On correlating the findings in the CTscan report, he was further referred to the Histopathology Department for Fine Needle Aspiration Cytology (FNAC) in view of definite diagnosis. Initial diagnosis on FNAC was given as chondrosarcoma in favour of the location of the swelling. Furthermore excision biopsy was done. The definitive diagnosis was given as dedifferentiated chondrosarcoma. FNAC of dedifferentiated lesions due to its rarity and limited experience poses a challenge to many histopathologists.